Analysis of Expression Pattern and Genetic Deletion of Netrin5 in the Developing Mouse - Garrett, Andrew M.; Jucius, Thomas J.; Sigaud, Liam P. R.; Tang, Fu-Lei; Xiong, Wen-Cheng; Ackerman, Susan L.; Burgess, Robert W. (Frontiers in Molecular Neuroscience, 2016)
Boundary cap cells are a transient, neural-crest-derived population found at the motor exit point and dorsal root entry zone of the embryonic spinal cord. These cells contribute to the central/peripheral nervous system boundary, and in their absence neurons and glia from the CNS migrate into the PNS. We found Netrin5 (Ntn5), a previously unstudied member of the netrin gene family, to be robustly expressed in boundary cap cells. We generated Ntn5 knockout mice and examined neurodevelopmental and boundary-cap-cell-related phenotypes. No abnormalities in cranial nerve guidance, dorsal root organization, or sensory projections were found. However, Ntn5 mutant embryos did have ectopic motor neurons that migrated out of the ventral horn and into the motor roots. Previous studies have implicated semaphorin6A (Sema6A) in boundary cap cells signaling to plexinA2 (PlxnA2)/neuropilin2 (Nrp2) in motor neurons in restricting motor neuron cell bodies to the ventral horn, particularly in the caudal spinal cord. In Ntn5 mutants, ectopic motor neurons are likely to be a different population, as more ectopias were found rostrally. Furthermore, ectopic motor neurons in Ntn5 mutants were not immunoreactive for NRP2. The netrin receptor DCC is a potential receptor for NTN5 in motor neurons, as similar ectopic neurons were found in Dcc mutant mice, but not in mice deficient for other netrin receptors. Thus, Ntn5 is a novel netrin family member that is expressed in boundary cap cells, functioning to prevent motor neuron migration out of the CNS.